Eric Williams: The historian as public intellectual. (5th January 2020) - St. Pierre, Maurice
Abstract: Eric Williams was an academic intellectual who authored the well‐regarded book Capitalism and Slavery, a public intellectual who left the academy to make his knowledge available to a wider audience or public in Trinidad and Tobago where he was born and, eventually, a social movement intellectual who led his country to political independence from Britain in 1962. This study focuses on Williams's efforts as a public intellectual to construct a public and space for his anticolonial renderings which became part of the public sphere.